A Scoping Review of Gaps Identified by Primary Care Providers in Caring for Patients with Chronic Noncancer Pain - Virginia McEwen; Mihal (Michelle); R. Gianni Lorello; Abhimanyu Sud; F. Marina Englesakis; Anuj Bhatia (Taylor & Francis Group, 2023)
ABSTRACTIntroduction/Aim Primary care providers (PCPs), who provide the bulk of care for patients with chronic noncancer pain (CNCP), often report knowledge gaps, limited resources, and difficult patient encounters while managing chronic pain. This scoping review seeks to evaluate gaps identified by PCPs in providing care to patients with chronic pain.Methods The Arksey and O'Malley framework was used for this scoping review. A broad literature search was conducted for relevant articles on gaps in knowledge and skills of PCPs and in their health care environment for managing chronic pain, with multiple search term derivatives for concepts of interest. Articles from the initial search were screened for relevance, yielding 31 studies. Inductive and deductive thematic analysis was adopted.Results The studies included in this review reflected a variety of study designs, settings, and methods. However, consistent themes emerged with respect to gaps in knowledge and skills for assessment, diagnosis, treatment, and interprofessional roles in chronic pain, as well as broader systemic issues including attitudes toward CNCP. A general lack of confidence in tapering high dose or ineffective opioid regimes, professional isolation, challenges in managing patients with CNCP with complex needs, and limited access to pain specialists were reported by PCPs.Discussion/Conclusions This scoping review revealed common elements across the selected studies that will be useful in guiding creation of targeted supports for PCPs to manage CNCP. This review also yielded insights for pain clinicians at tertiary centers for supporting their PCP colleagues as well as systemic reforms required to support patients with CNCP.